Fall-induced hospital-treated traumatic brain injuries among elderly Finns in 1970–2017. (January 2020) - Kannus, Pekka; Niemi, Seppo; Parkkari, Jari; Mattila, Ville; Sievänen, Harri
Highlights: Fall-induced hospital-treated TBI among elderly Finns increased considerably from 1970 to 2017. Rapid aging of the population will accelerate the problem further in the near future. The above noted facts call for urgent and wide-scale fall and injury prevention measures. Abstract: Background: Fall-induced traumatic brain injuries (TBI) of elderly adults are a major public health concern. Methods: We determined the current trends in the absolute number and incidence (per 100, 000 persons) of severe fall-induced TBI among 80-year-old or older Finns by taking into account all persons who were admitted to Finnish hospitals for primary treatment of such injury between 1970 and 2017. Results: The total number of hospitalized older Finns with a fall-induced TBI increased considerably between the years 1970 and 2017, from 60 (women) and 25 (men) in 1970 to 1622 (women) and 991 (men) in 2017. The age-adjusted incidence of TBI (per 100, 000 persons) also showed a clear increase from 1970 to 2017: from 167.9 to 800.4 in women (377% increase), and from 176.8 to 927.3 in men (424% increase). If this trend in the age-adjusted incidence of hospital-treated TBI continues, and the size of the 80-year-old or older Finnish population increases as predicted (from 0.29 million in 2017 to 0.49 million in 2030), the number of these severe injuries among 80-year-old or older Finns will be approximately 1.8 times higher in 2030 (4811 injuries) compared with 2613 injuries in 2017. Conclusions: The number and age-adjusted incidence of fall-induced hospital-treated TBI among elderly Finns increased considerably between 1970 and 2017. Wide-scale fall and injury prevention measures are urgently needed, because further aging of the population is likely to worsen the problem in the near future.